The Relationship between H. pylori Infection and Osteoporosis in Japan - Daisuke Asaoka; Akihito Nagahara; Mariko Hojo; Hitoshi Sasaki; Yuji Shimada; Takashi Yoshizawa; Taro Osada; Sumio Watanabe (Gastroenterology Research and Practice)
Background and Objective. H. pylori infection causes a chronic inflammation in the gastric mucosa. However, this local inflammation may result in extra-digestive conditions. Our aim is to investigate the relationship between H. pylori infection and osteoporosis in Japan. Methods. This cross-sectional study was conducted among outpatients at the Juntendo University Hospital between 2008 and 2014. Participants for patient profile, H. pylori infection status, comorbidity, internal medical therapies, lumbar dual-energy X-ray absorptiometry (DXA), and bone turnover marker were collected and upper gastrointestinal endoscopy for reflux esophagitis, hiatal hernia, peptic ulcer disease (PUD), and endoscopic gastric mucosal atrophy (EGA) was performed. The diagnosis of osteoporosis was performed in accordance with the Japanese criteria. We investigated risk factors of osteoporosis. Results. Of the eligible 200 study subjects, 41 cases were of osteoporosis. Bivariate analysis showed that age, being female, BMI, alcohol, smoking, H. pylori, bone-specific ALP, PUD, and EGA were related to osteoporosis. Multivariate analysis showed that age (OR 1.13; 95%CI 1.07–1.20), being female (OR 4.77; 95%CI 1.78–12.77), BMI (OR 0.79; 95%CI 0.68–0.92), H. pylori (OR 5.33; 95%CI 1.73–16.42), and PUD (OR 4.98; 95%CI 1.51–16.45) were related to osteoporosis. Conclusions. H. pylori infection may be a risk factor of osteoporosis in Japan.